Systemic Antibiotic Prophylaxis to Reduce Early Implant Failure: A Systematic Review and Meta-Analysis - Elisabet Roca-Millan; Albert Estrugo-Devesa; Alexandra Merlos; Enric Jané-Salas; Teresa Vinuesa; José López-López (Antibiotics, 2021)
Systemic antibiotics are routinely prescribed in implant procedures, but the lack of consensus causes large differences between clinicians regarding antibiotic prophylaxis regimens. The objectives of this systematic review are to assess the need to prescribe antibiotics to prevent early implant failure and find the most appropriate antibiotic prophylaxis regimen. The electronic search was conducted in PubMed/MEDLINE, Scielo and Cochrane Central Trials Database for randomized clinical trials of at least 3 months of follow-up. Eleven studies were included in the qualitative analysis. Antibiotics were found to statistically significantly reduce early implant failures (RR = 0.30, 95% CI: 0.19–0.47, p < 0.00001; heterogeneity I2 = 0%, p = 0.54). No differences were seen between preoperative or both pre- and postoperative antibiotic regimens (RR = 0.57, 95% CI: 0.21–1.55, p = 0.27; heterogeneity I2 = 0%, p = 0.37). A single preoperative antibiotic prophylaxis dose was found to be enough to significantly reduce early implant failures compared to no antibiotic (RR = 0.34, 95% CI: 0.21–0.53, p < 0.00001; heterogeneity I2 = 0%, p = 0.61). In conclusion, in healthy patients a single antibiotic prophylaxis dose is indicated to prevent early implant failure.